Consumers’ Consumption Values, Satisfaction and Loyalty Toward Mobile Payment Service Providers In China: Alternative Attractiveness As Moderator - Qi, Zhang (2023)
This study attempts to examine the relationship between consumers’ consumption values, satisfaction and loyalty by developing a framework based on the Cognitive-Affective- Behaviour (C-A-B) model and the Theory of Consumption Values (TCV).